Analisis Jual Beli Air Sumber Peninggalan Belanda dalam Menjamin Keabsahan Akad di Desa Dagangan; Prespektif Hukum Islam - Fahmi Putri Rahmadani (Institut Agama Islam Sunan Giri Ponorogo, 2023)
As living creature water is huge gift from Allah SWT. Humans as living creatures really need water, because water is a basic need in everyday life so the use of water has a big influence on meeting the increasing need for water. Of course, for areas tahat have barren and rocky soil and drought during the dry season, water needs are very limited. This thesis analyzes research with a problem statement: (1) What is the effectiveness of the practice of buying and selling sourced water in Dagangan Village (2) What is the prespective of Islamic law on the effectiveness of buying and selling water from Dutch heritage sources in ensuring the validity of contracts in Dagangan Village.This research is categorized as case study research. This research is based on the background of problem which is then reviewed using Islamic law and the data analyzed in this reserach is the Milles & Huberman interactive analysis model namely by analyzing data, reducting data, collecting data on the practice of buying and selling water from Dutch. Heritage sources in Dagangan Village, Dagangan District.The results of the practice of buying and selling water from Dutch heritage sources in Dagangan Village, in terms of Islamic law, is that in terms of the subject of buying and selling, buying and selling water from source is permitted because those doing the buying and selling are adults who are mumayyiz and there is no corecion. In the buying and selling. In terms of contact, the sale and purchase of source water in Dagangan Village is permitted because it is included in the transaction agreement which is permitted, namely verbally and does not cause disputes in the sale and purchase. In terms of objects, buying and selling source water in Dagangan Village is not permitted during the dry season because the amount of water in the community is limited